Model of Religious Character Education of Santri: A Case Study for the Character of Santri in Pesantren Syaichona Moh. Cholil - Mohammad Ruji (STAI Syaichona Moh. Cholil Bangkalan, 2022)
Ideals nation for shape generation young character _ no will achieved without supported by Islamic boarding schools in Indonesia. Character education no will formed without endorsement from various party, then from that role school both formal and non-formal (pesantren is very decisive to achievement ambition it. Study this aim for describe the models of religious education students who are applied in one of the Islamic boarding schools in Indonesia, namely PP. Syaichona Moh. Cholil, As part from contribution Pesantrenin build a developed and civilized country. Study this done with approach descriptive qualitative with method data collection interviews observations and documentation Through mils and hubbermen model analysis find results that the formation model character applied in the hut this integrated in obligations prohibitions and sanctions for those who violate rules. Effort for formation character that applied in ubudiyah, pesantren program and school program. Character education model applied in the cottage Pesantren syaichona cholil has succeed shape character religious students who are built on Foundation vision and mission Pesantrenwith strengthened by all cuttings existing houlder _ environment Pesantren